Dampak Gaya Kepemimpinan Transformasional Terhadap Kepuasan Kerja Pada ASN Milenial di Kementerian Perdagangan - Agus Setiyo Utomo; Andrika Pesparani Nikerija Nainggolan (Cendekia Niaga, 2020)
The study has aimed at identifying the impact between transformational leadership and job satisfaction of Milenial Generation civil servant, the population of the study consisted of registered Milinneal Generation civil servant located in Ministry of Trade. There have been 59 surveys mailed out to registered Milenial Generation civil servant. 59 surveys have been returned with an 100 % response rate. Regarding transformational leadership, the survey was adapted from the Multifactor Leadership Questionnaire (MLQ). The Minnesota Satisfaction Questionnaire (MSQ) developed by Weiss (1967) was adapted to measure job satisfaction. The present study has shown a statistically there is no relationship existing between the four dimensions of transformational leadership and the twentieth dimensions of job satisfaction. This study shows a positive and statistically significant relationship between the four dimensions of transformational leadership and twenty dimensions of job satisfaction. Keywords: Transformational leadership, job satisfaction, Millinneal Generation civil servant, Ministry of Trade.